Pericardial effusion under nivolumab: case-reports and review of the literature. Issue 1 (18th October 2019) - Saade, Anastasia; Mansuet-Lupo, Audrey; Arrondeau, Jennifer; Thibault, Constance; Mirabel, Mariana; Goldwasser, François; Oudard, Stéphane; Weiss, Laurence
Abstract : Background: Nivolumab, a programmed death-1 (PD-1) inhibitor, is an immune checkpoint inhibitor particularly used in the treatment of malignant melanoma, non-small cell lung cancer and renal cell carcinoma. Immune-related adverse events are frequent under immunotherapies. Cardiotoxic side effects, initially thought to be rare, are more often encountered paralleling the expanding use of immune checkpoint blockade. Among them, pericardial effusion and tamponade deserve attention as they may present with unusual symptomatology. Case presentation: We report three cases of pericardial effusion under nivolumab for lung adenocarcinoma. Two cases of early and late-onset pericardial effusion were symptomatic with tamponade and one case occurred without any symptoms. Pericardiocentesis with pericardial biopsy was performed in symptomatic pericardial effusion followed by the administration of a corticotherapy. Pericardial biopsies showed infiltration of T-lymphocytes, mostly CD4 + . Nivolumab was stopped in two cases and resumed for one patient. Pericardial effusion evolved positively in all cases with or without treatment. Conclusions: We review the literature on pericardial effusion under nivolumab to further discuss the hallmarks of pericardial effusion under nivolumab and the management of nivolumab therapy in this situation. In conclusion, pericardial effusion as an immune-related adverse event under nivolumab appears less rare than initially thought and may require particular attention.